2021
DOI: 10.1002/lt.26033
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Fatigue Persists in a Significant Proportion of Female Patients After Transplantation for Primary Sclerosing Cholangitis

Abstract: Chronic fatigue and an impairment of general health-related quality of life (HRQoL) are frequently reported by patients with primary sclerosing cholangitis (PSC). Studies on patients with primary biliary cholangitis (PBC) suggest that, unlike pruritus, fatigue may not be ameliorated by liver transplantation (LT). However, there are few data regarding the assessment of fatigue before and after transplantation in PSC. To investigate the effect of LT on fatigue and HRQoL in patients with PSC, 81 patients with PSC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Patient and graft survival in PSC are comparable with those transplanted for other liver diseases 374. In addition, transplantation results in substantial improvement in all aspects of quality of life,375–377 although fatigue persists in a significant proportion of female patients 378…”
Section: Management Of Pscmentioning
confidence: 94%
See 1 more Smart Citation
“…Patient and graft survival in PSC are comparable with those transplanted for other liver diseases 374. In addition, transplantation results in substantial improvement in all aspects of quality of life,375–377 although fatigue persists in a significant proportion of female patients 378…”
Section: Management Of Pscmentioning
confidence: 94%
“…[374] In addition, transplantation results in substantial improvement in all aspects of quality of life, [375][376][377] although fatigue persists in a significant proportion of female patients. [378] Given the potential risk of biliary strictures and CCA in the remnant duct, Roux-en-Y choledochojejunostomy has been the preferred method for biliary reconstruction. [379] Still, due to difficulties in managing biliary strictures in rPSC, there is a trend by some centers to perform duct-toduct anastomosis if the bile duct appears normal or in the absence of HGD at the time of transplantation.…”
Section: Lt For Cirrhosis/cholangitis/ccamentioning
confidence: 99%
“… 8 A prospective case-control study found that female patients were less likely to have improvement in fatigue after LT compared with male patients. 158 Further large-scale studies are required to further corroborate these findings and allow us to explore the potential of treating autonomic dysregulation and LT as a management of fatigue in PSC.…”
Section: Fatiguementioning
confidence: 97%
“…Focusing on lifestyle measures such as optimizing sleep hygiene and having a regular exercise regimen may assist in improving troublesome fatigue. 9 Although there is some data to suggest that LT significantly decreases chronic fatigue, 157 , 158 it is not currently an indication for LT as an isolated symptom. 8 A prospective case-control study found that female patients were less likely to have improvement in fatigue after LT compared with male patients.…”
Section: Fatiguementioning
confidence: 99%
“…Symptomatic patients present most commonly with fatigue, upper quadrant abdominal pain, and pruritus [85]. Recent studies showed that fatigue might persist after LT in female recipients [87]. A more aggressive presentation of the disease is characterized by recurrent episodes of biliary tract obstruction and subsequent cholangitis that may progress to cirrhosis, liver failure, or develop hepatobiliary malignancies [77,80].…”
Section: Primary Sclerosing Cholangitismentioning
confidence: 99%